2016
DOI: 10.1007/s00380-016-0823-0
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein(a) levels predict adverse vascular events after acute myocardial infarction

Abstract: Lipoprotein(a) [Lp(a)], which is genetically determined, has been reported as an independent risk factor for atherosclerotic vascular disease. However, the prognostic value of Lp(a) for secondary vascular events in patients after coronary artery disease has not been fully elucidated. This 3-year observational study included a total of 176 patients with ST-elevated myocardial infarction (STEMI), whose Lp(a) levels were measured within 24 h after primary percutaneous coronary intervention. We divided enrolled pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 33 publications
3
30
1
Order By: Relevance
“…Mitsuda et al used a different method in measuring serum Lp(a), the fixed-rate immunonephelometric method using JEOL JCA-BM8000 clinical chemistry analyzer (JEOL Inc., Tokyo, Japan). 28 Note that the cut-off points obtained by both researchers were based on long-term prediction of MACE. Other studies also used higher cut-offs (>30 mg/ dL), but these values were based on the prediction of coronary heart disease rather than MACE in acute AMI conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitsuda et al used a different method in measuring serum Lp(a), the fixed-rate immunonephelometric method using JEOL JCA-BM8000 clinical chemistry analyzer (JEOL Inc., Tokyo, Japan). 28 Note that the cut-off points obtained by both researchers were based on long-term prediction of MACE. Other studies also used higher cut-offs (>30 mg/ dL), but these values were based on the prediction of coronary heart disease rather than MACE in acute AMI conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The results also concluded that patients with high Lp(a) levels were at high risk of MACE and cerebrovascular events (HR 1.030, 95% CI 1.011-1.048, p = 0.002) and had a worse survival (log rank p = 0.034). 28 The study by Ikenaga et al assessed Lp(a) serum a week after AMI (total 410 patients) and divided it into two groups, high (> 40 mg/dL) and low (≤40 mg/dL). The MACE incidence for 5 years was significantly higher in the group with high Lp(a) levels compared to group with low Lp(a) levels.…”
Section: Discussionmentioning
confidence: 99%
“…Another recent study evaluated the association between Lp(a) levels and vulnerable plaque phenotype using optical coherence tomography (OCT) 25 ) . Mitsuda T et al reported lipoprotein (a) levels predict adverse vascular events in 176 patients with ST-elevated myocardial infarction during 3-year follow-up after primary PCI 26 ) . In contrast to these previous studies which included coronary revascularization in the primary endpoint, we focused the primary end-point on cardiac events defined as cardiac death and non-fatal acute coronary syndrome reflecting more coronary atherogenic property of Lp(a) with longer follow-up period.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated the relationship between Lp(a) levels and major adverse cardiac events (MACE) in patients with CVD. One study found that Lp(a) level at admission was an independent predictor of MACE in patients with ST‐segment elevation myocardial infarction . Another study reported that Lp(a) was associated with 1‐year risk of MACE, with an HR of 3.1 (95% CI: 1.1‐8.6), in patients after PCI .…”
Section: Discussionmentioning
confidence: 99%
“…One study found that Lp(a) level at admission was an independent predictor of MACE in patients with ST-segment elevation myocardial infarction. 11 Another study reported that Lp(a) was associated Data are presented as n (%) or mean AE SD. 7 In a study of 3251 older higher-risk adults, higher Lp(a) levels were associated with increases in risk of all CHD events when LDL-C was <70 mg/dL (HR: 2.68, 95%CI: 1.11-6.46).…”
Section: Several Studies Have Investigated the Relationship Betweenmentioning
confidence: 99%